Analisis Putusan MA Perkara No 916/Pdt.P/2022/PN.Sby Dalam Mengabulkan Permohonan Pencatatan Nikah Beda Agama Dalam Perspektif Undang-Undang Perkawinan No 1 Tahun 1974 - Hakim, Anwar; Soderi, Ridhokimura (Berasan: Journal of Islamic Civil Law, 2022)
Abstract: Interfaith Marriage in the Perspective of Marriage Law No. 1 of 1974 (Review of Analysis of Article 2 of Law No. 1 of 1974 concerning Marriage). Indonesia is a country with a multi-religious society. The various religions and beliefs held by the Indonesian people open up the potential for interfaith marriages. Interfaith marriages often cause polemics in society, this is because in Indonesia interfaith marriage is something that is considered uncommon and contrary to religious beliefs held by the majority of Indonesian people. In Indonesia, the rules related to marriage are contained in Law No. 1 of 1974 concerning Marriage and the Compilation of Islamic Law. Article 2 of the Marriage Law No. 1 of 1974 states that "a marriage is said to be valid if it is carried out according to the laws of each religion and belief". Problems arise when marriages are carried out by different religions and different beliefs, and the article does not mention interfaith marriages. The purpose of writing this scientific article is to examine and analyze the meaning related to these rules and other rules related to marriage in the Indonesian legal system, in order to determine and confirm the position of interfaith marriages according to Indonesian laws and regulations. This research is a normative research using the approach of legislation in Indonesia. Based on the analysis of the legal material obtained, interfaith marriage according to the marriage law in Indonesia is not allowed.